2018
DOI: 10.1111/bjh.15719
|View full text |Cite
|
Sign up to set email alerts
|

Developing role of B cells in the pathogenesis and treatment of chronic GVHD

Abstract: Summary Chronic graft‐versus‐host disease (cGVHD) is a major complication affecting the long‐term survival of patients after allogeneic haematopoietic stem cell transplantation. The mechanism of cGVHD is unclear, and while previous studies have primarily focused on T cells, the role of B cells in the pathogenesis of cGVHD has been less reported. However, current studies on cGVHD are increasingly focused on the important role of B cells. In this review, we will introduce the newest studies and examine the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 106 publications
0
16
0
Order By: Relevance
“…Sirolimus (SRL) is a mammalian target of rapamycin (mTOR) inhibitor that has been shown to induce apoptosis of both activated and irregular lymphocytes to promote tolerance (2,3). Consequently, SRL has emerged as one of the most promising immunosuppressive agents after transplantation of either solid organs or allogeneic stem cells (4).…”
Section: Introductionmentioning
confidence: 99%
“…Sirolimus (SRL) is a mammalian target of rapamycin (mTOR) inhibitor that has been shown to induce apoptosis of both activated and irregular lymphocytes to promote tolerance (2,3). Consequently, SRL has emerged as one of the most promising immunosuppressive agents after transplantation of either solid organs or allogeneic stem cells (4).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these studies were generally hampered by the development of graft versus host disease (GVHD) that arises in the context of MHC mismatch between donor and recipient cells. As it turns out, GVHD per se can cause the production of autoantibodies, confounding interpretations [ 20 , 21 ]. Other limitations observed in this model were the high numbers of mouse NK cells, which can directly limit human cell engraftment.…”
Section: Development and Improvement Of Human Immune System Micementioning
confidence: 99%
“…R Z et al [29] rituxan is studied in combination with large dose of chemotherapy in patients with NHL APBSCT treatment effect, the research object and Ⅳ follicular Ⅲ CD cells infusion, and to rebuild hematopoietic stem cells ability between the two groups, clinical adverse reactions and no obvious difference. X L et al [30] also confirmed that combined chemotherapy with rituximab could significantly reduce the contamination of lymphoma cells in mobilized stem cells, and the clinical and molecular remission rates of patients in the rituximab group were also significantly higher than those in the control group. Galimberti et al [31] 23 cases of follicular non-hodgkin's lymphoma patients APBSCT, including 13 cases with CHOP plan after chemotherapy in patients with high-dose chemotherapy alone, ll patients using high doses of chemotherapy in combination with rituxan treatment, the results showed that application of rituxan treatment group of Bel-2/IgH rearrangement negative rate was 86%, compared with high-dose chemotherapy control graft Bel-2/IgH rearrangement negative rate is 14.3%, the former EFS 5 years was 100%, and the lat-Open Journal of Blood Diseases ter is only 41%, This suggests that rituximab is an effective treatment for patients with follicular non-Hodgkin's lymphoma.…”
Section: Application Of Rituximab In Hematopoietic Stem Cell Transplamentioning
confidence: 86%